IP3R-dependent mitochondrial dysfunction mediates C5b-9-induced ferroptosis in trichloroethylene-caused immune kidney injury - Liu, Zhibing; Ma, Jinru; Zuo, Xulei; Zhang, Xuesong; Xie, Haibo; Wang, Feng; Wu, Changhao; Zhang, Jiaxiang; Zhu, Qixing (Frontiers in Immunology, 2023)
Patients with occupational medicamentose-like dermatitis due to trichloroethylene often suffer from immune kidney injury. Our previous study reveals that C5b-9-dependent cytosolic Ca2+ overload-induced ferroptosis is involved in trichloroethylene sensitized kidney injury. However, how C5b-9 causes cytosolic Ca2+ rise and the specific mechanism whereby overloaded Ca2+ induces ferroptosis remain unknown. The purpose of our study was to explore the role of IP3R-dependent mitochondrial dysfunction in C5b-9 mediated ferroptosis in trichloroethylene sensitized kidney. Our results showed that IP3R was activated, and mitochondrial membrane potential was decreased in the renal epithelial cells of trichloroethylene-sensitized mice, and these changes were antagonized by CD59, a C5b-9 inhibitory protein. Moreover, this phenomenon was reproduced in a C5b-9-attacked HK-2 cell model. Further investigation showed that RNA interference with IP3R not only alleviated C5b-9-induced cytosolic Ca2+ overload and mitochondrial membrane potential loss but also attenuated C5b-9-induced ferroptosis in HK-2 cells. Mechanistically, IP3R-dependent cytosolic Ca2+ overload activated the mitochondrial permeability transition pore, resulting in the loss of mitochondrial membrane potential and ferroptosis of HK-2 cells. Finally, cyclosporin A, a mitochondrial permeability transition pore inhibitor, not only ameliorated IP3R-dependent mitochondrial dysfunction but also blocked C5b-9-induced ferroptosis. Taken together, these results suggest that IP3R-dependent mitochondrial dysfunction plays an important role in trichloroethylene sensitized renal tubular ferroptosis.